Analysis of numerical modelling of turbulence in a conical reverse‐flow cyclone - Vaitiekūnas, Petras; Jakštonienė, Inga (Journal of Environmental Engineering and Landscape Management, 2010)
This paper aims to analyse the problem of numerical modelling of the airflow in a conical reverse‐flow (CRF) cyclone with tangential inlet (equipment for separation of solid particles from gaseous fluid flow). A review of experimental and theoretical papers that describe cyclones with very complex swirling flow is performed. Three‐dimensional transport differential equations for incompressible turbulent flow inside a cyclone are solved numerically using finite volume‐based turbulence models, namely, the Standard k–ϵ model, the RNG k–ϵ model and the Reynolds stress model (RSM). The paper describes the numerical modelling of the airflow in the CRF cyclone, the height of which is 0.75 m, diameter – 0.17 m, height of cylindrical part – 0.255 m, height of conical part – 0.425 m, inlet area is 0.085 × 0.032 m2. Mathematical model of airflow in a cyclone consisted of Navier‐Stokes (Reynolds) three‐dimensional differential equation system. Modelling results, obtained from the numerical tests when inlet velocity is 4.64, 9.0 and 14.8 m/s and flow rate is, respectively, 0.0112, 0.0245 and 0.0408 (0.0388) m3/s, have demonstrated a reasonable agreement with other authors’ experimental and theoretical results. The average relative error was ± 7.5%. Article in English. Dujų aerodinamikos kūginiame turbulentinio grįžtamojo srauto ciklone skaitinio modeliavimo analizė Santrauka. Nagrinėjama dujų aerodinamikos kūginiame grįžtamojo srauto (KGS) ciklone (įrenginys kietosioms dalelėms atskirti iš oro srauto) su tangentiniu srauto įtekėjimu skaitinio modeliavimo problema. Trimatės nespūdžiojo turbulentinio srauto ciklono viduje pernašos diferencialinės lygtys skaitiškai spręstos baigtinių tūrių metodu taikant standartinį k–ϵ, RNG k–ϵ ir Reinoldso įtempių (RIM) turbulencijos modelius. Atliktas skaitinis oro srauto judėjimo KGS ciklone modeliavimas. Ciklono aukštis – 0,75 m, skersmuo – 0,17 m, cilindrinės dalies aukštis – 0,255 m, kūginės – 0,425 m, įtekėjimo angos plotas 0,085×0,032 m2. Oro srauto judėjimo ciklone matematinis modelis – Navjė ir Stokso (Reinoldso) trimačių diferencialinių lygčių sistema. Modeliavimo rezultatai, kai įtekėjimo greitis 4,64, 9,0 bei 14,8 m/s ir debitas – 0,0112, 0,0245 ir 0,0408 (0,0388) m3/s, neblogai sutapo su kitų autorių eksperimentiniais rezultatais. Vidutinė santykinė paklaida – ± 8 proc. Reikšminiai žodžiai: ciklonas, kietosios dalelės, skaitinis modeliavimas, turbulentumas, vienfazis, dvifazis oro srautas. Анализ численного моделирования турбуленции возвратного потока в коническом циклоне Резюме. Анализируется проблема аэродинамики газового потока в коническом возвратного потока (КВП) циклоне (оборудование для отделения твердых частиц от газового потока) с тангенциальной подачей газа. Произведен обзор экспериментальных и теоретических работ в циклонах такого типа, в которых образуется сложное вихревое течение потока. Для моделирования использованы трехмерные дифференциальные уравнения переноса, численно решаемые методом конечных объемов с использованием следующих моделей: стaндартной k–ϵ, RNG k–ϵ и Рейнольдсовой модели турбулентности напряжений. Произведено численное моделирование движения потока воздуха в циклоне КВП, высота которого 0,75 м, диаметр – 0,17 м, высота цилиндрической части – 0,255 м, конической части – 0,425 м, площадь входного отверстия – 0,085×0,032 м2 . Математическую модель движения потока воздуха в циклоне составила система трехмерных дифференциальных уравнений Навье-Стокса и Рейнольдса. Анализ результатов, произведенный при скоростях втекания в циклон 4,64, 9,0 и 14,8 м/с (дебит – 0,0112, 0,0245 и 0,0408 м3/с) и для модели рейнольдсовых напряжений, показал приемлемую согласованность с результатами других исследователей – со средней относительной погрешностью ± 7,5 проц. Ключевые слова: циклон, твердые частицы, численное моделирование, турбулентность, одна фаза, двухфазовый поток флюида. First Publish Online: 10 Feb 2011